Women's empowerment and fertility preferences in high fertility countries in Sub-Saharan Africa - Esso-Hanam Atake; Pitaloumani Gnakou Ali (BMC, 2019)
Abstract Background Nearly all countries with fertility levels of more than five children per woman are in Sub-Saharan Africa. Prestige, insurance in old age, and replacement in case of child deaths are related to preferences for large families. In this paper, we examine the association between women's empowerment and fertility preferences of married women aged 35 years and above in four high fertility Francophone Sub-Saharan Africa (FSSA) countries, namely Burkina Faso, Mali, Niger and Chad. Method The ideal number of children among married women and their ability to have the desired number of children are used to measure fertility preferences. We used principal component analysis to construct a multidimensional empowerment index. We then estimated negative binomial and logistic regression models to examine the association between women's empowerment and fertility preferences. Data are from the most recent Demographic and Health Surveys (DHS) conducted in the countries included in the analysis. Results Regardless of the country, more empowered women desire significantly fewer children compared with their less empowered counterparts. The first step to having fewer children is formulating programs to improve economic empowerment of women. The specific elements of women's empowerment that were important for fertility preferences included education, skills development, decision-making power, and control over household resources. In addition, familial empowerment matters more than other dimensions of empowerment in influencing women's ability to achieve the desired number of children in the FSSA countries included in the study. Conclusion Paid employment and access to and control over resources are factors which, if improved upon, could significantly reduce the ideal number of children. By taking necessary steps, mass media can be used much more adequately to reduce ideal number of children in FSSA countries. In addition, the desire for many children could also be due to their participation in income-generating activities to improve the household's socio-economic status. The findings suggests that improvement of women's ability to have the desired number of children is a big challenge to which policy makers must pay careful attention.